2011
DOI: 10.1038/onc.2010.600
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of androgen receptor activity by histone deacetylase 4 through receptor SUMOylation

Abstract: The transcriptional activity of the androgen receptor is regulated by both ligand binding and posttranslational modifications including acetylation and SUMOylation. Histone deacetylases are known to catalyze the removal of acetyl groups from both histones and non-histone proteins. In the present study, we report that histone deacetylase 4 (HDAC4) binds to and inhibits the activity of the androgen receptor (AR). This inhibition was found to depend on the SUMOylation, instead of deacetylation, of the AR. Consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 40 publications
1
37
0
1
Order By: Relevance
“…MTT Cytotoxicity Assay and Crystal Violet Staining-For MTT assay, cells were treated as indicated with TRAIL alone or pretreated with CT for 12 h, washed with PBS, and then treated with TRAIL for an additional 24 h. Then, the effects of CT on TRAIL-induced cytotoxicity were determined by the MTT uptake method (17). For crystal violet staining assay, cells (1 ϫ 10 5 ) were seeded in 60-mm dishes and then untreated or pretreated with CT for 12 h, washed with PBS, and then treated with TRAIL.…”
Section: Methodsmentioning
confidence: 99%
“…MTT Cytotoxicity Assay and Crystal Violet Staining-For MTT assay, cells were treated as indicated with TRAIL alone or pretreated with CT for 12 h, washed with PBS, and then treated with TRAIL for an additional 24 h. Then, the effects of CT on TRAIL-induced cytotoxicity were determined by the MTT uptake method (17). For crystal violet staining assay, cells (1 ϫ 10 5 ) were seeded in 60-mm dishes and then untreated or pretreated with CT for 12 h, washed with PBS, and then treated with TRAIL.…”
Section: Methodsmentioning
confidence: 99%
“…The genetic interaction between HDAC4 and Ubc9 was particularly interesting as a growing body of evidence indicates that SUMOylation is an important mechanism for regulation of neuronal protein activity (Henley et al 2014) and for regulation of memory formation (Yang et al 2012;Castro-Gomez et al 2013;Luo et al 2013;Chen et al 2014;Wang et al 2014;Drisaldi et al 2015). Moreover, HDAC4 has also been implicated as a putative E3 SUMO ligase, as its presence enhances the SUMOylation of MEF2 (Gregoire and Yang 2005;Zhao et al 2005) and of the androgen receptor (Yang et al 2011) in mammalian cells. To further explore the link between HDAC4 and SUMOylation, we investigated the interaction of HDAC4 with Ubc9 and other members of the SUMOylation machinery (Table 4).…”
Section: Hdac4 Interacts With the Sumoylation Machinerymentioning
confidence: 99%
“…As HDAC4 is itself a target of sumoylation, it has been suggested that a sumoylation cascade may take place, yet a SUMO-deficient HDAC4 can still promote AR-Su (Yang et al 2011b).…”
Section: Ar-sumoylationmentioning
confidence: 99%